L-Canavanine potentiates the cytotoxicity of doxorubicin and cisplatin in arginine deprived human cancer cells - Nurcahyanti, Agustina DR; Wink, Michael (PeerJ, 2016)
The non-protein amino acid L-canavanine (L-CAV), an antimetabolite of L-arginine (L-ARG), can alter the 3D conformation of proteins when incorporated into a protein instead of L-ARG. L-CAV inhibits the proliferation of some tumour cells. The deprivation of L-ARG in the culture medium enhances the response of cells to L-CAV. This study aimed to investigate the interaction of L-CAV in combination with the chemotherapeutic drugs, doxorubicin (DOX) or cisplatin (CIS), in cancer cells, especially in the absence of L-ARG. A combination method based on the median-effect principle and mass-action law was used. The following cancer cells were employed: HeLa and Caco-2 cells, overexpressing argininosuccinate synthase (ASS), pancreatic cells (MIA PaCa-2 and BxPC-3) and hepatocellular carcinoma cells (Hep G2 and SK-HEP-1), with down-regulated ASS. When constant and non-constant ratios of L-CAV were combined with DOX and CIS, a synergistic potentiation of cytotoxicity was recorded. Cells expressing high levels of ASS were more sensitive to the treatment as compared to the cells with reduced ASS levels. Overall, this study may provide a new approach to targeting some cancer cells with L-CAV in combination with DNA-targeting drugs such as DOX and CIS, especially those cells which overexpress ASS, such as human cervical and colorectal carcinoma cells.
Keywords: L-canavanine; L-arginine; Doxorubicin; Cisplatin; Argininosuccinate synthase (ASS); Synergy